If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 49 + 3x Reorder the terms: 9 + 7x = 49 + 3x Solving 9 + 7x = 49 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + 7x + -3x = 49 + 3x + -3x Combine like terms: 7x + -3x = 4x 9 + 4x = 49 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 4x = 49 + 0 9 + 4x = 49 Add '-9' to each side of the equation. 9 + -9 + 4x = 49 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 49 + -9 4x = 49 + -9 Combine like terms: 49 + -9 = 40 4x = 40 Divide each side by '4'. x = 10 Simplifying x = 10
| 25x^2-24x-9=-7x^2+12-18 | | 6=x/65 | | 2x-6=7x+14 | | 4x+14=-8x-2(7-4x) | | 36+8a=3(3a+1) | | -5x-9y=45 | | x-6=2x+5 | | 5-7(8y+6)= | | 11(2-9)+99-10(2)= | | 13k-130=201 | | 3x+5=-19+7x | | x-5=2x+5 | | -37/16=v/32 | | x-5(27-x)= | | 12x^2=-10x+5 | | 5(n+3)+11n=2+3n | | x(4x-5)-3=3 | | 5+6x=3x+29 | | X-4(x+13)= | | Inx+Inx^8=9 | | Log(x-1)+log(x+1)=0 | | 5(3x)=4 | | 9x=12x+1 | | -3x+32=5 | | 5x+1=4x+10 | | 3x+12=-80-10x | | 11x-7=10x+4 | | 15+3x=9+6x | | 5-(5y+8)=5y+3 | | sin(3x+pi)=0 | | -3(-2(-5)+2)+6(-5)-4(2)= | | 4x+3(2x-1)-4x=25 |